Geographical Information SCIENCE : Case Studies in Earth and Environmental Monitoring - Petropoulos, George P.; Chalkias, Christos (Elesvier, 2024)
Geographic Information Systems: Case Studies in Environmental Monitoring provides detailed remote sensing and GIS methods, algorithms and technology comparisons focusing on a wide range of environmental applications. The geoinformation technologies are demonstrated through templated case studies detailing real world use of the techniques and clarifying methods, tools and practical solutions to environmental mapping and monitoring. The book utilizes remote sensing and geospatial data from the most recently launched satellites,and applies the latest geospatial data approaches and analysis software tools (both commercial and open source).